"MESE" FUNDAMENTAL AS BEST HUMAN INTERIOR DESIGNER - Andereas, P S (Journal of Engineering and Scientific Research, 2019)
Interior designer is a profession that is most responsible for the whole series of human activities on this earth. It is very important to place this concept because all important aspects of the human life in this space are fully in contact with the profession of interior designer. The education of interior designing is not just about creating ideas on how to create beauty and design spaces, but also about having responsibilities on various aspects in life. In the era of digitalization and where the components of life become increasingly complex, interior designers must be able to play the appropriate role to solve life?s problems. The developments in various aspects of ecology are also connected to interior designers, for example, recycling the waste must be one of interior designer?s goals. Experimenting, innovating, and becoming part of social life is the actual responsibility of interior designer, not living in the works of hedonism.